2009
DOI: 10.1158/1541-7786.mcr-08-0589
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of CXCL13 to Stimulate RANK Ligand Expression in Oral Squamous Cell Carcinoma Cells

Abstract: Oral squamous cell carcinomas (OSCC) are malignant tumors with a potent activity of local bone invasion/ osteolysis. The chemokine ligand, CXCL13, has been identified as a prognostic marker for OSCC development and progression. Here in, we show that recombinant hCXCL13 treatment of OSCC cells stimulates (5-fold) RANK ligand (RANKL), a critical bone resorbing osteoclastogenic factor expression. Anti-CXCR5 chemokine receptor antibody abrogates CXCL13-induced RANKL expression in these cells. Also, CXCL13 stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Where present in the epithelial tissue (33.64% of all sections irrespective of diagnosis), CXCL13 antigen was located in the cytoplasm, though staining was barely above background in most cases, and no trend with disease severity was observed. Within the stromal tissue, however, CXCL13 antigenicity was much more apparent in OSCC than NOM, a result that is in keeping with other cancers [43,44], reflected in reports that CXCL13 gene expression is part of the gene signature for PMOL [6,9] and OSCC [19], and supports the functional role of CXCL13 in OSCC invasion [45].…”
Section: Discussionsupporting
confidence: 73%
“…Where present in the epithelial tissue (33.64% of all sections irrespective of diagnosis), CXCL13 antigen was located in the cytoplasm, though staining was barely above background in most cases, and no trend with disease severity was observed. Within the stromal tissue, however, CXCL13 antigenicity was much more apparent in OSCC than NOM, a result that is in keeping with other cancers [43,44], reflected in reports that CXCL13 gene expression is part of the gene signature for PMOL [6,9] and OSCC [19], and supports the functional role of CXCL13 in OSCC invasion [45].…”
Section: Discussionsupporting
confidence: 73%
“…We thus explored RANKL-inducing agents from a wide range of growth factors as well as inflammatory cytokines; however, failed to identify it so far. CXCL13 can certainly upregulate RANKL (Yuvaraj et al, 2009), albeit less efficiently compared to the upregulation observed in vivo (unpublished result). In the future, we believe that through our observations and the unveiling of remaining associated issues, the establishment of more rational, potent anti-cancer therapy with consideration of the communication between cancer cells and their respective microenvironment will eventually be accomplished.…”
Section: Resultsmentioning
confidence: 85%
“…CXCL13 (BCA-1) that binds monogamously to the CXCR5 receptor was originally discovered to facilitate B-cell chemotaxis (Legler et al, 1998). CXCL13 can upregulate receptor activator of NF-B ligand (RANKL), a member of the tumor necrosis factor family critical for osteoclastogenesis (Hsu et al, 1999), through activation of c-Jun N terminus kinase and nuclear factor of activated T cells (NFAT)-4, implicating CXCL13 as a potential biomarker to predict OSCC bone invasion or osteolysis (Yuvaraj et al, 2009). …”
Section: Inflammatory Cytokines and Chemokinesmentioning
confidence: 99%
“…Further, JNK activity has been shown to be required for STAT activation [56,57]. We previously showed that a JNK inhibitor abrogates the CXCL13 stimulated RANKL expression in oral cancer cells [12]. Therefore, TRAIL induction of JNK activation may play a role in STAT6 activation to enhance RANKL expression.…”
Section: Discussionmentioning
confidence: 95%
“…Also, DNA methylation has been shown to play an important role in modulation of RANKL and osteoprotegerin (OPG) expression in human bone [11]. We previously identified NFATc3 as a downstream target of CXCL13 signaling pathway to stimulate RANKL expression in oral squamous cell carcinoma cells [12]. Similarly, increased levels of extracellular calcium induced RANKL expression through activation of NFATc3 in mouse osteoblast cells [13].…”
Section: Introductionmentioning
confidence: 99%